Rare disasters and the equity premium in a two-country world - Laurence Copeland; Yanhui Zhu (Cardiff University, Cardiff Business School, 2007)
We extend the Barro (2006) closed-economy model of the equity risk premium in the presence of extreme events (disasters) to a two-country world. In this more general setting, both the output risk of rare disasters and the associated risk of a default on Government debt, can be diversiÖed. The extent to which agents in one country can diversify away the risk of extreme events depends on the relative size of the two countries, and critically on the probability of a disaster in one country conditional on a disaster in the other. We show that, using Barroís own calibration in combination with a broad range of plausible values for the additional parameters, the model implies levels of the equity risk premium far lower than those typically observed in the data. We conclude that the model is unlikely to explain the equity risk premium.
Keywords: F3; G1; 330; equity risk premium; default risk; international diversification; Risikoprämie; Kapitalertrag; Risikoaversion; Schock; Wirtschaftskrise; Theorie